2023
DOI: 10.1111/ecog.06783
|View full text |Cite
|
Sign up to set email alerts
|

Continental‐scale climatic gradients of pathogenic microbial taxa in birds and bats

Yanjie Xu,
Anbu Poosakkannu,
Kati M. Suominen
et al.

Abstract: The connections of climatic variables to zoonotic and wildlife diseases remain uncertain. Here, we compiled a systematic database for the prevalence of 121 pathogenic microbial taxa in birds (ca 376 species) and bats (ca 39 species), including 11 939 observations from over 450 000 individuals across Europe and surrounding regions. We modelled the potential connection of climatic variables with the prevalence of 75 pathogenic microbial taxa at a multi‐pathogenic‐taxa level and of 17 most‐studied pathogenic taxa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…increased temperature and precipitation) are hypothesized to drive this pattern [ 21 ]. A recent study modelling potential connections between climate variables and pathogen prevalence has also suggested that elevated temperatures and greater precipitation will accelerate the transmission of bird- and bat-associated bacteria or viruses to wild and domesticated animals and humans [ 22 ]. One example of the potential impact of this process was the recent COVID-19 pandemic, where a SARS-CoV-2 progenitor virus that probably originated in southeast Asian horseshoe bats ( Rhinolophus sp.)…”
Section: Effects Of Climate Change On Eid Transmissionmentioning
confidence: 99%
“…increased temperature and precipitation) are hypothesized to drive this pattern [ 21 ]. A recent study modelling potential connections between climate variables and pathogen prevalence has also suggested that elevated temperatures and greater precipitation will accelerate the transmission of bird- and bat-associated bacteria or viruses to wild and domesticated animals and humans [ 22 ]. One example of the potential impact of this process was the recent COVID-19 pandemic, where a SARS-CoV-2 progenitor virus that probably originated in southeast Asian horseshoe bats ( Rhinolophus sp.)…”
Section: Effects Of Climate Change On Eid Transmissionmentioning
confidence: 99%
“…In the Nearctic, large die-offs have only been reported in three species (M. lucifugus, M. septentrionalis, P. subflavus) (Cheng et al 2021). It is important to comprehend that the overlap in distribution of the host and the pathogen is likely greater than the distribution range for the incidence of the disease causing mortality (Xu et al 2023). Furthermore, high incidence of mortality appears to be restricted to a proportion of the overlapping distribution range, where factors contributing to disease intercede favourably.…”
Section: Wnd Of Change In the Nearcticmentioning
confidence: 99%

The Palearctic view on a bat fungal disease

Whiting-Fawcett,
Blomberg,
Troitsky
et al. 2023
Preprint
“…This emphasizes the importance of understanding the microbiota of migratory birds and bats, and the prevalence of pathogens within the microbiota across geographical locations and habitats. Information such as this would also allow for a better understanding of the impact of climate change, such as temperature and rainfall alterations on pathogen prevalence in birds and bats 12 , and to predict the threat of disease outbreaks via modeling approaches.…”
mentioning
confidence: 99%